Marcas de luxo no varejo de confecção: fatores de influência sobre a decisão de compra do consumidor - Rodrigues, Flaviana Maria Viana (2012)
This study aims to generally prove that the motivation and productivity variables in the group companies Panebox are positively related. It was initially performed a literature search that enabled them to greater certainty of the relationship between productivity and motivation. Then, we applied a questionnaire used as the basis for the development of case study in the group companies Panebox, this instrument that can evaluate the degree of employee motivation. The data collected and studied in a quantitative way to provide data for analysis and conclusion. According to the results, behavioral factors, such as interpersonal relationships and job satisfaction were highlighted relevant, proving the influence of motivation on productivity.